2017
DOI: 10.1021/acs.orglett.7b00184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ring-Fused 1-Benzazepines via [1,5]-Hydride Shift/7-Endo Cyclization Sequences

Abstract: Synthesis of 1-benzazepines has been achieved via a [1,5]-hydride shift/7-endo cyclization sequence. The focus of this research is a direct transformation of 2-(aryl)cyclopropane 1,1-diester derivatives into 1-benzazepines using a cyclopropane moiety as the hydride acceptor in internal redox reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…For instance, Wang [11] developed a method for the construction of benzo[ b ]azepines via copper‐catalyzed oxidative C( sp 3 )−H/C( sp 2 )−H cross‐coupling (Scheme 1a). Kim [12] reported the Lewis acid catalyzed synthesis of ring‐fused 1‐benzazepine derivatives from 2‐(aryl)cyclopropane 1,1‐diesters via [1,5]‐hydride shift/cyclization sequences (Scheme 1b). In 2018, Shi [13] disclosed a Ni‐catalyzed method for the preparation of benzo[ b ]naphtho[1,2‐ d ]azepines via intramolecular cyclization of alkyl bromide‐tethered alkylidenecyclopropanes (Scheme 1c).…”
Section: Figurementioning
confidence: 99%
“…For instance, Wang [11] developed a method for the construction of benzo[ b ]azepines via copper‐catalyzed oxidative C( sp 3 )−H/C( sp 2 )−H cross‐coupling (Scheme 1a). Kim [12] reported the Lewis acid catalyzed synthesis of ring‐fused 1‐benzazepine derivatives from 2‐(aryl)cyclopropane 1,1‐diesters via [1,5]‐hydride shift/cyclization sequences (Scheme 1b). In 2018, Shi [13] disclosed a Ni‐catalyzed method for the preparation of benzo[ b ]naphtho[1,2‐ d ]azepines via intramolecular cyclization of alkyl bromide‐tethered alkylidenecyclopropanes (Scheme 1c).…”
Section: Figurementioning
confidence: 99%
“…Kim et al. reported the Lewis acid‐catalyzed [1,5]‐hydride shift and subsequent 7‐ endo cyclization of DAC‐containing cyclic amine 151 to furnish 1‐benzazepines 152 (Scheme a) . In this protocol, the cyclopropane moiety is used as the hydride acceptor in the internal redox reaction.…”
Section: Synthesis Of Seven‐ and Eight‐membered Nitrogen Heterocyclesmentioning
confidence: 99%
“…Kim and co‐workers recently reported that donor–acceptor cyclopropane moieties could act as hydride acceptors (Scheme ) . In the presence of Lewis acid catalysts, tertiary amines 63 bearing a donor–acceptor cyclopropane group could undergo a [1,5]‐hydride transfer process, thus generating a zwitterion intermediate M34 that is available for 7‐ endo cyclization.…”
Section: Redox‐neutral Iminium Approachmentioning
confidence: 99%
“…[55] Kim and co-workersr ecently reported that donor-acceptor cyclopropane moieties could act as hydride acceptors (Scheme 27). [56] In the presence of Lewis acid catalysts, tertiary amines 63 bearing ad onor-acceptor cyclopropane group Scheme22. Gold-catalyzed cyclization involving ah ydridet ransfer process.…”
Section: Scheme21 Alkyne Acts As Hydride Acceptormentioning
confidence: 99%